Fibonacci’s Computation Methods vs Modern Algorithms - Burattini, Ernesto (Reti Medievali Rivista, 2013)
<!–[if gte mso 9]> Normal 0 14 false false false MicrosoftInternetExplorer4 <![endif]–> In this paper we discuss some computational procedures given by Leonardo Pisano Fibonacci in his famous Liber Abaci book, and we propose their translation into a modern language for computers (C ++). Among the other we describe the method of “cross” multiplication, we evaluate its computational complexity in algorithmic terms and we show the output of a C ++ code that describes the development of the method applied to the product of two integers. In a similar way we show the operations performed on fractions introduced by Fibonacci. Thanks to the possibility to reproduce on a computer, the Fibonacci’s different computational procedures, it was possible to identify some calculation errors present in the different versions of the original text. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>